Effects of moringa stenopetala (Baker f.) Cufod leaf on reproductive organs and serum biochemical levels in male rats: An in vivo reproductive toxicity study - Hussen Abdu; Wondwosen Ergete; Ashenif Tadele; Samuel Woldekidan; Abiy Abebe; Mehari Meles; Melese Shenkut; Girma Seyoum (Phytomedicine Plus, 2023)
Background: Moringa stenopetala (Baker f.) Cufod. (Moringaceae) leaves are a common food source and traditional medicine used to treat a variety of illnesses, including malaria, hypertension, stomach discomfort, diabetes, elevated cholesterol, and the removal of the retained placenta. Its reproductive toxicity studies are limited. Therefore, the objective of the current study was to examine the toxicity of a 70% ethanol extract of Moringa stenopetala leaf on the reproductive organs and serum biochemical levels in male Wistar rats. Method: Fresh leaves of Moringa stenopetala were extracted using 70% ethanol. For this study, five groups of animals, each containing twenty rats, were used. Groups I - III were treated with 250, 500, and 1000 mg/kg body weight of Moringa stenopetala leaf extract, respectively. Groups IV and V were pair-fed and ad libitum control groups. The extract was given for ten weeks. Data about body weights, weights and histology of reproductive organs, testosterone, LH, and FSH, levels, and serum chemistry were analyzed using one-way ANOVA, Tukey's test, and Dunnett's test. Results: Compared to the pair-fed control group, the sex hormones like testosterone, FSH, and LH levels increased in the 1000 mg/kg body weight treated rats. Significant differences were not seen in the weight and histology of the testis, epididymis, prostate gland, or seminal glands. However, the serum ALT, AST, ALP, HDL, and creatinine levels were significantly raised in the high-dose-treated group. Conclusion: Moringa stenopetala may increase reproductive hormones in male rats. Consuming Moringa stenopetala leaves could therefore help to increase male reproduction.